Analysis of Management of Santri Mini Bank (BMS) on Quran Memorization Institute Foundation Islamic Centre North Sumatra - Margolang, Yusrinaldi Rahman; Rahmayati (LP2M IAIN Palopo, 2025)
The purpose of this study is to analyze financial managementSantri Mini Bank (BMS) inQuran Memorization Center FoundationIslamic Center of North Sumatra. BMS is here as a solution to students' financial problems, such as sending funds from guardians and the risk of losing money.The methods used are those that have a case study approach through interviews, observations and documentation. The results showThe manual system creates operational challenges such as queues and delays in disbursement of funds. Digitization through e-money and information technology-based record-keeping is recommended to improve efficiency, transparency, and accountability. With the right strategy, BMS has the potential to become a secure and educational financial system for Islamic boarding school students.